Peran TPS3R dalam Pengelolaan Sampah Botol Plastik di Kota Bogor: Studi Kasus Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS3R) Eco Techno Park Universitas IBN Khaldun Bogor - Usep Saripudin; Rimun Wibowo; Gunawan Ismail; Najamudin Najamudin (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
Plastic waste, particularly plastic bottles, has become one of the major challenges in urban environmental management due to its increasing volume and potential to pollute ecosystems. In Bogor City, plastic waste constitutes a significant proportion of daily municipal solid waste, highlighting the need for effective and sustainable waste management models. This study aims to analyze the role of the Reduce, Reuse, Recycle Waste Processing Facility (TPS3R) in managing plastic bottle waste in Bogor City, with a case study of the Eco Techno Park at Ibn Khaldun University (UIKA) Bogor. The research employed a descriptive qualitative method using a case study approach. Data were collected through field observations, in-depth interviews with facility managers, and reviews of relevant documents and literature. The findings indicate that the TPS3R Eco Techno Park has successfully implemented the 3R principles through an integrated system supported by environmentally friendly technologies and a circular economy framework. Plastic bottle waste is managed through sorting, shredding, and recycling processes to produce value-added products, including plastic pellets, handicrafts, and construction materials. In addition, organic waste management is integrated through the cultivation of Black Soldier Fly (BSF) larvae. The facility has contributed to reducing the volume of waste sent to landfills by approximately 18%. The study implies that strengthening regulatory support, enhancing community participation, and developing circular economy-based business models are essential to ensure the long-term sustainability of waste management programs and support Bogor City's waste reduction targets.